2017
DOI: 10.17557/tjfc.311012
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF DIFFERENT WATER AND NITROGEN APPLICATIONS ON SOME YIELD PARAMETERS AND ANTIOXIDANT ACTIVITY IN SAGE (Salvia officinalis L.)

Abstract: The effect of different water and nitrogen applications on some yield parameters and antioxidant activity on sage (Salvia officinalis L. var. Extrakta) was investigated. A field trial was arranged in the split plot design with four replications under the Bornova ecological conditions in 2012 and 2013. The following water regimes were used as main plots: S1 (irrigated when it's needed), S2 (20 days dry before harvesting) and S3 (40 days dry before harvesting) and nitrogen applications were used as sub-plots suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
6
11
1
Order By: Relevance
“…The researcher noted the variety of essential oil components depending on the harvest time. Current findings on the chemical constituents of S. officinalis volatile oil are in line with several previous investigations (Bettaieb et al, 2009;Mossi et al, 2011;Govahi et al, 2015;Sönmez and Bayram, 2017). Numerous factors affect the quality of the volatile oil, which are hard to be determined and distinct from each other.…”
Section: Volatile Oil Content and Chemical Componentssupporting
confidence: 88%
See 3 more Smart Citations
“…The researcher noted the variety of essential oil components depending on the harvest time. Current findings on the chemical constituents of S. officinalis volatile oil are in line with several previous investigations (Bettaieb et al, 2009;Mossi et al, 2011;Govahi et al, 2015;Sönmez and Bayram, 2017). Numerous factors affect the quality of the volatile oil, which are hard to be determined and distinct from each other.…”
Section: Volatile Oil Content and Chemical Componentssupporting
confidence: 88%
“…Various nutrient sources improve soil chemical and physical characteristics. Several studies supported that nitrogen and other nutrients sources application intensified on total fresh yield and aerial parts of S. officinalis (Ghoushchi et al, 2015;Gerami et al, 2016;Sönmez and Bayram, 2017;Hegab et al, 2018). It was reported that the application of cow manure, vermicompost, Azotobacter, and Azospirillum increased the final yield of S. officinalis compared to the control treatment (Radnezhad et al, 2015).…”
Section: Fresh and Dry Herb Weightmentioning
confidence: 92%
See 2 more Smart Citations
“…Salvia officinalis L. (common sage), as a woody perennial herb, is one of the most important commercial species of the genus Salvia which includes nearly 1000 species throughout the Old and New Worlds (Lakušić et al 2013). Salvia officinalis is native to the Mediterranean region but does not exist naturally in Turkey (Sönmez & Bayram 2017). The cultivation of S. officinalis has recently become common in different regions of Turkey.…”
Section: Introductionmentioning
confidence: 99%